The Investigator : Letty Davenport #1 - Sandford, John, 1944 February 23- (New York : G.P. Putnam's Sons, 2022)
"Letty Davenport, the brilliant and tenacious adopted daughter of Lucas Davenport, takes the investigative reins in the newest thriller from #1 bestselling author John Sandford"--.
New Book 2022 Spring.
Keywords: Davenport, Lucas (Fictitious character); Criminal investigation; Oil industries; Petroleum industry and trade; Detective and mystery fiction; Novels